In vivo characterization of 3D-printed polycaprolactone-hydroxyapatite scaffolds with Voronoi design to advance the concept of scaffold-guided bone regeneration - Laubach, Markus; Herath, Buddhi; Bock, Nathalie; Suresh, Sinduja; Saifzadeh, Siamak; Dargaville, Bronwin L.; McGovern, Jacqui; Wille, Marie-Luise; Hutmacher, Dietmar W.; Medeiros Savi, Flavia (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional (3D)-printed medical-grade polycaprolactone (mPCL) composite scaffolds have been the first to enable the concept of scaffold-guided bone regeneration (SGBR) from bench to bedside. However, advances in 3D printing technologies now promise next-generation scaffolds such as those with Voronoi tessellation. We hypothesized that the combination of a Voronoi design, applied for the first time to 3D-printed mPCL and ceramic fillers (here hydroxyapatite, HA), would allow slow degradation and high osteogenicity needed to regenerate bone tissue and enhance regenerative properties when mixed with xenograft material. We tested this hypothesis in vitro and in vivo using 3D-printed composite mPCL-HA scaffolds (wt 96%:4%) with the Voronoi design using an ISO 13485 certified additive manufacturing platform. The resulting scaffold porosity was 73% and minimal in vitro degradation (mass loss <1%) was observed over the period of six months. After loading the scaffolds with different types of fresh sheep xenograft and ectopic implantation in rats for eight weeks, highly vascularized tissue without extensive fibrous encapsulation was found in all mPCL-HA Voronoi scaffolds and endochondral bone formation was observed, with no adverse host-tissue reactions. This study supports the use of mPCL-HA Voronoi scaffolds for further testing in future large preclinical animal studies prior to clinical trials to ultimately successfully advance the SGBR concept.